A Survey of Cancer Pain Management Knowledge and Attitudes of British Columbian Physicians - R Gallagher; P Hawley; W Yeomans (Pain Research and Management)
INTRODUCTION: There are many potential barriers to adequate cancer pain management, including lack of physician education and prescription monitoring programs. The authors surveyed physicians about their specific knowledge of pain management and the effects of the regulation of opioids on their prescribing practices.